A NEW REPRESENTATIVE OF THE FAMILY RAOELLIDAE (SUIFORMES) FROM THE MIDDLE EOCENE OF KHAICHIN-ULA 2, MONGOLIA - Vislobokova I.A. (My University, 2004)
The Middle Eocene fauna of Khaichin-Ula 2 is shown to include a new species of the genus Haqueina of the family Raoellidae. In addition to this form, the fauna includes three suiform species, Gobiohyus reshetovi, G. pressidens, and Chorlakkia valerii. New morphological data on Haqueina corroborate the validity of the family Raoellidae and allow for the analysis of its relationships.
Keywords: Artiodactyla; Suiformes; Middle Eocene; Mongolia; new species; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен